Study of the behavior of snails intermediate hosts of Schistosoma spp. under different maintenance conditions and their resistance to salinity in an african laboratory environment. Issue 8 (August 2022) - Thiam, Fatou; Fall, Cheikh Bintou; Gaye, Papa M.; Senghor, Bruno; Diamanka, Arfang; Wotodjo, Amélé N.; Abotsi, Kokou; Parola, Philippe; Faye, Babacar; Sokhna, Cheikh; Sow, Doudou; Doucouré, Souleymane
Abstract: Background: The control of snails intermediate hosts remains an effective strategy to limit schistosomiasis transmission despite the widespread mass de-worming campaign based on praziquantel. Therefore, the study of snail biology could help to improve snails control strategies. This study evaluated the development of Biomphalaria pfeifferi, Bulinus senegalensis and Bulinus truncatus in various water sources and their resistance to salinity. Methods: Five day-old juveniles individuals issued from adult snails non-shedding Schistosoma spp cercariae were breed in distilled water, commercial mineral water, ground pump water and well water. Snail's survival rate and size were measured over a period of 40 days. These two parameters were also measured over 30 days in increasing saline solutions (1 g/l, 3.5 g/l and 4 g/l) made of well water to which sodium chloride was added. Results: B. truncatus growth was not hampered by any water sources with a survival rate between 68% and 84% (log rank X 2 = 1.86, df = 3, p = 0.60). Despite a poor survival rate (8%) in distilled water, B. pfeifferi, has adapted to other water sources with a survival fraction between 88% and 96% (log rank X 2 = 61.94, df = 3, p < 0.0001). B. senegalensis development was very delicate with low survival rate of 4% in distilled water, 20% in well water and 24% in commercial mineral water and ground pump water (log rank X 2 = 13.24, df = 3, p = 0, 004). For each species, even if the difference is not significant, the size of snails is larger with well water and pump water compared to distilled and commercial mineral water. B. pfeifferi survival rate was at 45% in both three saline solutions at day 30. B. senegalensis population collapsed at day 10 in 4 g/l saline solution and persisted until day 30 in both 1.5 g/l and 3.5 g/l solution. B. truncatus also persisted with a survival rate at 20% in 1.5 g/l but collapsed at day 5 and 15 in 4 g/l and 3.5 g/l solution, respectively. Conclusion: The differences in adaptation between snails species show the need to take into account the water sources for snail breeding in the laboratory. Further studies could help to determine the optimal water quality for each snail species in order to standardize breeding conditions. This study could contribute to the understanding of the dynamics and distribution of snails in natural conditions. Graphical abstract: Snails field collection, laboratory rearing and size measurement system. Highlights: The knowledge of snail breeding conditions could represent a breakthrough for schistosomiasis control The survival rate of B. truncatus, B. senegalensis and B. pfeifferi depended on the origin of the water used for snails breeding Only B. truncatus displayed relatively high survival rate to both distilled water, commercial mineral water, ground pump water and well water The survival of B. pfeifferi is less hampered in saline water compared to B. truncatus and B. senegalensis Abstract : Snail; Schistosomiasis; Water; Salinity; Survivor; Size.